Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Pada Perusahaan Manufaktur Di BEI - Steven Sanjaya, Rosmita Rasyid (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this study is to find out the effects of corporate social responsibility, profitability, capital structure, and firm size on firm’s value in manufacturing companies listed on the Indonesian Stock Exchange 2015-2017. This research uses 63 manufacturing companies that have been selected through a purposive sampling method of a total 136 companies over three years and resulting 189 samples data. The data used are secondary data which includes financial statements and company annual reports. Processing carried out in this study uses Eviews version 9 software. The results of this study indicate that corporate social responsibility, and capital structure have a significant effect on the increase in firm’s value, but for profitability, and firm size does not significantly influence on firm’s value.